Autologous peripheral blood stem cell transplantation in dialysis‐dependent multiple myeloma patients—DAUTOS Study of the Polish Myeloma Study Group. (4th July 2018) - Waszczuk‐Gajda, Anna; Lewandowski, Zbigniew; Drozd‐Sokołowska, Joanna; Boguradzki, Piotr; Dybko, Jarosław; Wróbel, Tomasz; Basak, Grzegorz Władysław; Jurczyszyn, Artur; Mądry, Krzysztof; Snarski, Emilian; Frączak, Ewa; Charliński, Grzegorz; et al.
Abstract: Introduction: Dialysis‐dependent (DD) multiple myeloma patients (MM) have a poor prognosis and high tumour burden, thus may benefit from autologous peripheral blood stem cell transplantation (auto‐PBSCT), however, these patients have an increased risk of toxicity. Aims: To evaluate the outcomes (toxicity, PFS, OS) of high dose therapy followed by auto‐PBSCT during an observational study and after propensity score matching. Patients and methods: Between 2004‐2015, 24 DD patients, (aged 38‐67 years), ISS 3, treated with auto‐PBSCT, requiring dialysis at diagnosis and auto‐PBSCT were evaluated, matched and compared to 55 normal renal function MM patients (NRF) with ISS 3 for outcomes of interest. Results: In DD patients compared to NRF patients risk of mucositis (88% vs 55%), infection (79% vs 51%), parenteral nutrition (50% vs 24%), diarrhoea (71% vs 38%), prolonged duration of hospitalisation (medians: 30 vs 21 days), requirement for RBC transfusion (83% vs 36%) were significantly higher, while no significant differences were found in post‐transplant response (ORR; 75% vs 87%), 5‐year PFS (36% vs 20%) and OS (39% vs 50%). Subgroup analyses based on toxicity supported these results. Conclusions: Despite the increased risk of toxicity in DD patients these events do not significantly affect both the PFS and OS.